CREAM-Pushing the high energy frontier of directly measured cosmic rays - O. Ganel; H. S. Ahn; P. Allison; M. G. Bagliesi; J. J. Beatty; BIGONGIARI, GABRIELE; P. Boyle; J. T. Childers; N. B. Conklin; S. Coutu; M. A. Duvernois; J. H. Han; et al. (Czechoslovak Journal of Physics, 2006)
After nearly a century since their discovery, much is still uncertain about cosmic rays, including their source, acceleration mechanism, and propagation. Direct measurement of cosmic-ray elemental spectra in the critical energy range of 10(12) - 10(15) eV offers a promising avenue to answering these questions. The Cosmic Ray Energetics And Mass (CREAM) experiment was launched from McMurdo Station, Antarctica, under a NASA research balloon on December 16, 2004. Floating for nearly 42 days at altitudes between 36 and 39 km, CREAM collected over 4 x 10(7) events. Preliminary results show great promise for this dataset. CREAM-II launched on December 16, 2005 and flew for 28 days. A refurbished CREAM is planned to fly again in 2007. This presentation will examine the experimental context of CREAM, describe the detector, and show preliminary results from accelerator beam tests and the first flight.